Anthropometric variations in different BMI and adiposity levels among children, adolescents and young adults in Kolkata, India. Issue 4 (4th December 2018) - Kryst, Łukasz; Żegleń, Magdalena; Wronka, Iwona; Woronkowicz, Agnieszka; Bilińska-Pawlak, Inez; Das, Rituparna; Saha, Rana; Das, Sukanta; Dasgupta, Parasmani
Abstract: The objective of the study was to analyse selected anthropometric features of children, adolescents and young adults from middle-class families in Kolkata, India, by BMI and adiposity categories. Standardized anthropometric measurements of 4194 individuals (1999 male and 2195 female) aged 7–21 were carried out between the years 2005 and 2011. The results were compared by BMI and adiposity categories. Statistical significance was assessed using two-way-ANOVA and linear regression analysis was performed. The study population could be differentiated in terms of BMI and adiposity categories for all examined anthropometric characteristics ( p ≤ 0.001). After taking age into consideration, differences were observed for males in the case of body height and humerus breadth in BMI and adiposity categories, and for femur breadth in the case of adiposity categories. For females, differences were noted in body height measurements in BMI and adiposity categories, a sum of skinfold thicknesses in BMI categories, and upper-arm and calf circumferences in adiposity categories. The patterns of differences in the BMI categories were found to be similar to those in adiposity categories. The linear regression analysis results showed that there was a significant relationship between BMI and body fat ratio in the examined population. Underweight individuals, and those with low adiposity, were characterized by lower extremity circumferences and skeletal breadths. These features reached highest values in overweight/obese persons, characterized by high body fat. However, the differences observed between each BMI and adiposity category, in most cases, were only present in early childhood.